Be Unstoppable : The Eight Essential Actions to Succeed at Anything - Mills, Alden M. (Book collections on Project MUSE., 2013)
The author "uses the power of storytelling and his own experiences as a Navy SEAL and seasoned entrepreneur to teach his proven framework for success," in an allegory with action-based strategy.